Matematicas en Jupiter - Linde, Barbara M.; Jimenez, Alberto (New York : Gareth Stevens Publishing, 2017)
Provides an introduction to Jupiter, including the planet's rings and moons.
English title: Math on Jupiter.
Includes bibliographical references and index.
2-5.
7-10.
Keywords: Mathematics -- Juvenile literature; Spanish language; Jupiter (Planet) -- Juvenile literature